Diabetic Neuropathy: A Clinical and Neuropathological Study of 107 Patients - David S. Younger (Neurology Research International)
One hundred seven patients were retrospectively studied from 1992 to 2002 with diabetic neuropathy that underwent peripheral nerve biopsy. Nerve biopsy revealed the underlying histopathology, including cell and humoral-mediated immunological lesions in the majority of patients. When combined with clinical and laboratory studies, nerve biopsy has the potential to assist in the selection of patients who may benefit from immunomodulatory therapy.